2006
DOI: 10.1071/wr05039
|View full text |Cite
|
Sign up to set email alerts
|

The propensity of spotted-tailed quolls (Dasyurus maculatus) to encounter and consume non-toxic meat baits in a simulated canid-control program

Abstract: Using a biomarker, we assessed the propensity of spotted-tailed quolls (Dasyurus maculatus) to encounter and consume non-toxic meat baits, ordinarily laced with the poison 1080 (sodium monofluoroacetate) and deployed for control of wild dogs (Canis lupus dingo, Canis familiaris and hybrids of the two) in southern Australia. In the first experiment, 60 unpoisoned meat baits injected with Rhodamine B were placed on the surface of the ground at 250-m intervals along two separate transects crossing an open woodlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…McIlroy 1982b; Murray and Poore 2004) are not sufficient for predicting the impact of 1080-baiting campaigns on populations (King 1989;Claridge and Mills 2007;Körtner 2007). Therefore, determination of theoretical risk should be regarded only as a first step in assessing the actual risk faced by non-target species (King 1989;Körtner et al 2003;Körtner and Watson 2005;Claridge et al 2006;Claridge and Mills 2007;Körtner 2007). Without monitoring the fate of individual animals and populations during the actual baiting campaigns, any risk assessments of baiting remain highly speculative and can lead to erroneous management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…McIlroy 1982b; Murray and Poore 2004) are not sufficient for predicting the impact of 1080-baiting campaigns on populations (King 1989;Claridge and Mills 2007;Körtner 2007). Therefore, determination of theoretical risk should be regarded only as a first step in assessing the actual risk faced by non-target species (King 1989;Körtner et al 2003;Körtner and Watson 2005;Claridge et al 2006;Claridge and Mills 2007;Körtner 2007). Without monitoring the fate of individual animals and populations during the actual baiting campaigns, any risk assessments of baiting remain highly speculative and can lead to erroneous management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…It appears likely that none of the radio-collared quolls died of acute 1080 poisoning, but most quolls had eaten 1080 dog baits and survived bait consumption. Hence, under natural conditions quolls are probably less prone to fatal poisoning than laboratory-based toxicology studies (McIlroy 1981) and simulation trials using non-toxic baits laced with rhodamine B have suggested (Murray and Poore 2004;Claridge et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, after a relatively short period baits will cease to be lethal to quolls (and other species, as illustrated by the rhodamine B-positive cats). Hence it is unlikely that bait-consumption figures derived from rhodamine B markings over relatively long periods during simulation trials could be extrapolated to mortality rates during toxic baiting campaigns (Claridge et al 2006). Second, the LD 50 s of 1080 (dose rate at which 50% of the studied population died) for quolls and other species were generally obtained by infusing a purified 1080 solution into test animals (McIlroy 1981).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations